2022
DOI: 10.1038/s41598-022-25436-3
|View full text |Cite
|
Sign up to set email alerts
|

Skin dysbiosis and Cutibacterium acnes biofilm in inflammatory acne lesions of adolescents

Abstract: Acne vulgaris is a common inflammatory disorder affecting more than 80% of young adolescents. Cutibacterium acnes plays a role in the pathogenesis of acne lesions, although the mechanisms are poorly understood. The study aimed to explore the microbiome at different skin sites in adolescent acne and the role of biofilm production in promoting the growth and persistence of C. acnes isolates. Microbiota analysis showed a significantly lower alpha diversity in inflammatory lesions (LA) than in non-inflammatory (NI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 110 publications
(163 reference statements)
3
17
1
Order By: Relevance
“…Since the patients in the 4–6 years group did not use any antibiotics in the past 6 months, the decrease we observed is less likely due to the medication. Changes in alpha diversity between acne and normal groups were not consistent in the previous research 32–34 . Variations in these studies may be explained by the disease time of recruited individuals.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…Since the patients in the 4–6 years group did not use any antibiotics in the past 6 months, the decrease we observed is less likely due to the medication. Changes in alpha diversity between acne and normal groups were not consistent in the previous research 32–34 . Variations in these studies may be explained by the disease time of recruited individuals.…”
Section: Discussioncontrasting
confidence: 84%
“…Changes in alpha diversity between acne and normal groups were not consistent in the previous research. [32][33][34] Variations in these studies may be explained by the disease time of recruited individuals. In the present study, we also found that the alpha diversity of microbial communities increased in the skin pore.…”
Section: Discussionmentioning
confidence: 99%
“…There were two reports investigating Chinese acne patients’ skin microbiota suggested that the alpha diversity of skin microbiota in the acne group is greater than that in the healthy control group, while beta diversity also showed differences ( Li et al, 2019 ; Shi et al, 2021 ). However, there were reports found that the diversity of skin microbiota in the acne group is no different from that in the healthy group, and even reports suggested that the diversity of skin microbiota in acne patients is significantly reduced ( Cavallo et al, 2022 ). Recently, a report from Korea revealed that there was no difference in the diversity between acne and healthy group ( Kim et al, 2021 ), which was consistent with this study that only a slight difference was found in the beta diversity of fungal flora between the different grade acne group and the health group ( Table 2 ; Figure 2 ; Supplementary Figures S1 – S4 ).…”
Section: Discussionmentioning
confidence: 99%
“…47,48 The formation of biofilm and secretion of virulence factors (CAMP haemolysis, lipase, RoxP enzyme) by C. acnes phylotype IA 1 stimulates production of interleukin-17 by Th17 lymphocytes. 47,49 Thus, the various C. acnes phylotypes can modulate T-cell responses leading to either acne development or homeostasis. 47…”
Section: Update On C Acnes and S Epidermidis In Acnementioning
confidence: 99%